Parâmetros genéticos populacionais como indicadores de sustentabilidade em populações naturais de pimenta rosa - Schinus terebinthifolius RADDI. (Anacardiaceae) no baixo curso do rio São Francisco - SE/AL - Carvalho, Sheila Valéria álvares (2009)
The conservation of forest species requires the prior knowledge of genetic parameters belonging to the population, to help to design strategies for this purpose. This study aimed to evaluate genetic parameters and suggest indicators of sustainability in populations of Schinus terebinthifolius Raddi. aiming the conservation and maintenance of diversity in this species. In analysis of the study area, were selected 20 descriptors, and these suggested 20 indicators of sustainability for the area. Tender vegetal leaves were sampled in five populations located on the shores and islands of São Francisco River, and the material collected from 15 individuals for each population. In the DNA extraction it was used tender leaves of individuals and 2% CTAB method. We applied 20 primers of 10 bases of arbitrary sequence in amplification, the products were separated in agarose gel at 1% submitted to horizontal electrophoresis, stained with ethidium bromide and visualized in ultraviolet light. The presence and absence of bands were used to construct a binary matrix for the analysis of genetic parameters. In each population the percentage of polymorphic loci ranged from 32.92% to 45.34%. The average gene diversity of Nei was 0.37. The total genetic variation observed, 63.60% corresponded to variation among populations, and 36.40% within populations. The gene flow (Nm) estimated was 0.28. Thus the conclusion is the populations are genetically isolated, and analyzed the genetic parameters can be used as indicators of sustainability of the area.